Review Facility Development of Aircraft Tire Retreading in Indonesia - Freddy Franciscus (Jurnal Teknologi Kedirgantaraan, 2020)
Aircraft tire retread is the process of retreading or reconditioning aircraft tires after being used several times for take off and landing. Retreading an aircraft tire can be done many times, which is between 3-5 times depending on the level of wear of the tire layer. Data from INACA ‘Indonesia AviationOutlook 2017’ shows that the number of jet aircraft owned by Indonesian airlines for Wide Body is 23 aircraft and Narrow Body is 338 aircraft. Where the number of aircraft tyre in the Nose Landing Gear / NLG and Main Landing Gear / MLG Wide Body aircraft are 55 EA and 216 EA respectively, while for Narrow Body aircraft each is 352 EA and 1488 EA. The available information states that tire retreading needs in Indonesia are around USD 20 million per year. There is a huge opportunity in the need for retreading aircraft tires owned by Indonesian airlines, which is around USD 20 million per year, with 10% growth per year, so the next 5 years will reach around USD 30 million. However, this opportunity cannot be taken by MRO Indonesia because MRO Indonesia does not have the ability to retread airplane tires. The cause of the inability to take up an aircraft tire retreading business opportunity is partly because there is no government policy support to encourage aircraft tire manufacturers to collaborate with Indonesian investors to build a tire retread facility, there is business competition with aircraft tire retreading in Malaysia and Thailand, businesses most only think solely of big profits, and the unattractive business climate in Indonesia such as complicated licensing, inefficient supply chains and incentives provided are less attractive. The steps needed to capture the opportunity to retread aircraft tires are to carry out continuous campaigns and incorporate aircraft tire retread facilities development programs into the National Strategic Program and the Aerospace Industry Roadmap.